Suture type used for perineal injury repair and sexual function: a randomised controlled trial - Martínez-Galiano, Juan Miguel (Sci Rep, 2020)
The type of suture used to repair perineal injury may be associated with this healing process and subsequent sexual function. This study aims to assess whether the suture technique used (continuous or interrupted) has an impact on a woman’s sexual function following childbirth. A single-blind randomised clinical trial was conducted with primiparous women who had experienced a perineal injury during childbirth. A computer-generated random number table was applied to allocate women to each group. Data were collected on sociodemographic variables, variables associated with childbirth, and outcomes during the 3 months after childbirth. Mean difference was used to assess the influence of the suture type on outcomes. Multivariate analyses were carried out to adjust for unbalanced variables after randomisation. Seventy women participated in the intervention group (continuous suture) and 64 women in the control group (interrupted suture). The women in the intervention group scored high for sexual desire, adjusted mean difference (aMD) = 1.8, 95% CI = 1.1–2.6 (p < 0.001); the same happened with arousal (aMD = 1.7, 95% CI = 0.8–2.5, p < 0.001). In the intervention group, orgasm was more easily reached, aMD = 0.8, 95% CI = 0.4–1.1 (p < 0.001). Women who received a continuous suture indicated they felt less discomfort (p < 0.001). Women who had a continuous suture reported better postpartum sexual function. Trial registration: ClinicalTrials.gov NCT03825211 posted 31/01/ 2019.